A facile route to prepare functional mesoporous organosilica spheres with electroactive units for chiral recognition of amino acids. Issue 2 (9th November 2018) - Wu, Datong; Tan, Wensheng; Li, Hongda; Lei, Zhangchen; Deng, Linhong; Kong, Yong
Abstract : Functional mesoporous organosilica spheres with electroactive units were prepared for chiral recognition of amino acids. Abstract : Conductive materials are valuable supports and widely applied in electrochemical analysis. In the current article, a mesoporous organosilica sphere( S, S )-CPMO-3 with the chiral group and electroactive units is presented. The organosilicon framework is composed of free ions belonging to the ionic liquid and the chiral group arising from (1 S, 2 S )-1, 2-diaminocyclohexane. Next, a bare electrode was modified by the as-synthesized composite material to construct the new electrochemical sensor( S, S )-CPMO-3-GCE . It was observed that( S, S )-CPMO-3-GCE exhibited favourable enantioselective recognition in the response of the peak current ( I p ) and the peak potential ( E p ) to the different configurations of amino acids. Taking tryptophan as an example, the value of I L / I D is 13.84 and the peak-to-peak potential approaches 48 mV. In addition, cysteine and tyrosine were successfully distinguished by the sensor. In summary, this study not only introduces a route for the synthesis of a conductive material, but also opens up its further potential in enantioselective recognition.